2017
DOI: 10.1128/jvi.02147-16
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4 + T Cell Responses to an Attenuated Tetravalent Dengue Vaccine Parallel Those Induced by Natural Infection in Magnitude, HLA Restriction, and Antigen Specificity

Abstract: Dengue virus (DENV) is responsible for growing numbers of infections worldwide and has proven to be a significant challenge for vaccine development. We previously demonstrated that CD8 ϩ T cell responses elicited by a dengue live attenuated virus (DLAV) vaccine resemble those observed after natural infection. In this study, we screened peripheral blood mononuclear cells (PBMCs) from donors vaccinated with a tetravalent DLAV vaccine (TV005) with pools of dengue virusderived predicted major histocompatibility co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 33 publications
2
93
0
Order By: Relevance
“…Here we compared the magnitude and breadth of the response and the response rates of CD8 T cells observed in the monovalent DLAV studies (12) with those of CD8 T cells observed in the current study. A similar analysis at the level of CD4 responses was not feasible since the CD4 immunogenicity of the attenuated viruses was evaluated only with the tetravalent formulation (8).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here we compared the magnitude and breadth of the response and the response rates of CD8 T cells observed in the monovalent DLAV studies (12) with those of CD8 T cells observed in the current study. A similar analysis at the level of CD4 responses was not feasible since the CD4 immunogenicity of the attenuated viruses was evaluated only with the tetravalent formulation (8).…”
Section: Resultsmentioning
confidence: 99%
“…This effect has been reported in the context of other viral systems. A similar comparison of the various DLAVs and rDEN2Δ30 at the level of CD4 responses was not feasible since the CD4 immunogenicity of the attenuated viruses was evaluated only with the tetravalent formulation (8). Since no clinical evaluation of monovalent DLAVs is currently ongoing, samples for study were no longer available for our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations